An Analysis of The Planning of The Direct Regional Election in The New Normal Period (A Conceptual Study on The Implementation of the Regional Election in Tidore) - Sangadji, Suwandi S; Rachman, Saiful (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2021)
This study aimed to find out the planning, challenges, rational vision and mission offers, and the implementation of the 2020 regional election in Tidore during the new normal period. The applied method in this study was descriptive-qualitative using an interactive model approach. The results of this study can be stated with the following conclusions. (1) In the context of planning and preparation for the 2020 regional election in Tidore, it is necessary to pay attention to the successes and possible failures of the 2019 general election by setting a transparent and integrated planning and preparation concept for all parties who will determine the success of this regional election; (2) The general challenge faced by the government and the people of Tidore, especially for the Regional General Election Commission (in Indonesian: Komisi Pemilihan Umum Daerah (KPUD)) in organizing the 2020 regional elections, is how to carry out the regional elections democratically based on the direct, general, free, secret, honest, and fair principles as a process of maturing public political behavior; (3) The special challenge faced by each pair of candidates is to offer a concept of a realistic, actual, accurate, and precise development vision and mission according to the development, needs, potentials, and problems of the people of Tidore.